Responsible Tourism: Peran dan Dampak Penyelenggaraan Jember Fashion Carnaval (JFC) dalam Pembangunan Berkelanjutan - Kalingga Wenna Ferliqueena Paramitha; Bambang Suharto (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The Jember Fashion Carnaval (JFC) has grown into one of Indonesia's most significant cultural and fashion events, even gaining international fame. In addition to increasing Jember's tourism appeal, JFC also creates business opportunities for local communities. However, like many other cultural events, JFC needs help balancing economic growth and tourism with sustainable development principles. This study aims to analyze the role and impact of JFC in supporting sustainable local tourism development in Jember. Using a descriptive qualitative approach, the research included observations and interviews involving various resource persons involved in implementing JFC, including the organizing foundation, workers, and visitors. The results show that JFC contributes significantly to sustainably advancing local tourism, with cooperation between organizers, government, and audiences driving economic growth and increasing the number of tourist visits in Jember. Despite supporting the promotion of culture and the welfare of local communities, aspects of environmental development such as waste management, resource use, and carbon emissions still require further attention. This study concludes that JFC is essential in sustainable local tourism development. Still, improvements are needed in environmental aspects to support more sustainable development of JFC through better environmental management, social inclusion, and empowerment of local communities.